Ultra-efficient and durable photoelectrochemical water oxidation using elaborately designed hematite nanorod arrays. (September 2017) - Jeon, Tae Hwa; Moon, Gun-hee; Park, Hyunwoong; Choi, Wonyong
Abstract: Ultrahigh-efficiency photoelectrochemical water oxidation using modified hematite (α-Fe2 O3 ) nanorod arrays is reported. The hematite nanorod arrays are synthesized using chemical bath deposition and further modified by hydrogen treatment, loading of a 3.5-nm-thick TiO2 overlayer, and deposition of a cobalt phosphate (CoPi) catalyst. Although each modification method is well known, an elaborate optimization of the combined modification methods achieves a stable photocurrent density of 6 mA cm −2 at 1.23 V vs. RHE over 100 h under AM 1.5G irradiation (100 mW cm −2 ) with the stoichiometric O2 and H2 evolutions at 95% of Faradaic efficiency. To the best of our knowledge, this is the highest photocurrent density obtained using a hematite-based photoanode, and such long-term durability coupled with this level of efficiency has been rarely reported. The modified-hematite photoanodes are thoroughly characterized using various spectroscopic and electrochemical techniques. While the hydrogen treatment enhances the electrical conductivity, the ultrathin TiO2 overlayer reduces the surface charge recombination and effectively preserved the integrity of the hydrogen-treated hematite electrode. Graphical abstract: Highlights: Hematite nanorod arrays doped with hydrogen and coated with an ultrathin TiO2 layer are synthesized. An optimized hematite exhibits unprecedented photocurrents of 6 mA cm −2 at 1.23 V over 100 h. O2 is linearly produced from water with a current efficiency of 100% without deactivation for 100 h. A stoichiometric amount of H2 was simultaneously produced.